Perinatal neurological results of patients ailing from advanced eclampsia and preeclampsia: A retrospective study - Aykan Gulleroglu; Melike Korkmaz Toker; Ayse Gul Karabay; Ilhan Guney Bicer; Mustafa Tayfun Aldemir (Medicine Science, 2018)
Preeclampsia/eclampsia is a contributing factor for high rates of maternal mortality worldwide. Data suggests that cerebral haemorrhage is a major cause of death among individuals suffering from preeclampsia. In this research, data was collected for over three years from pregnant women who were undergoing treatment at perinatology intensive care unit. They were admitted due to severe and uncontrolled eclampsia and preeclampsia. This research seeks to determine the frequency of patients who displayed cerebrovascular events, their clinical presentations and neuroimaging abnormalities. A retrospective evaluation of all obstetric patients who were diagnosed as pregnancy induced hypertension and followed-up between January 2011 and 2014 was performed. Retrospective computer records of age, neurologic symptom and neuroimaging findings were recorded and examined. Of the 222 participants in the study, 26 were diagnosed with severe preeclampsia while 10 patients have eclampsia. The study was performed on 36 patients whose age are ranking between 17 and 42 with a mean age of 30.06 ± 5.77. Mean systolic blood pressure was 156.89 ± 26.48 mmHg; and the average diastolic blood pressure was 98.29 ± 23.13 mm Hg. Of the 36-severe preeclampsia and eclampsia participants, 18 had begun to exhibit neurological attributes arising from eclampsia and pregnancy induced hypertension. Most common presenting symptom was generalized tonic-clonic seizures (eight, 44%). Five women had cerebral infarction and only one case had intraventricular haemorrhage. Two patients died after eclampsia crisis related intraparenchymal haemorrhage. Women ailing from advanced systolic hypertension (160 mm Hg) and severe eclampsia or preeclampsia have a higher risk of developing haemorrhagic stroke. Cerebral haemorrhage and stroke occurring in pregnancy and puerperium is a severe complication that can lead to maternal death. There should be recognition of using CT in those cases that are refractory to antihypertensive therapy can be lifesaving. [Med-Science 2018; 7(4.000): 831-3]